Resource-Based View Theory Application on the Educational Service Quality - Hemaloshinee, Vasudevan A. (Researcher Index Publication, 2021)
— Background and Objectives: The purpose of this study is to review the resource-based view theory on service quality that contribute to and expand internal resources and services of high quality. Several empirical studies have examined how to apply resource-based view theory to exploiting opportunities in higher education. With the help of this resource-based view theory, urban higher education can apply how to obtain and mobilize additional resources or use existing resources more efficiently and effectively to increase the productivity of existing resources to improve the quality of education services. Perhaps providing high-quality service based views are hampered by a lack of resources for urban education institutions and new ventures, and for them to survive, the resource constraints should address effectively. The issue in this paper is how the RBV theory or concept is to be studied in urban higher education so that researchers and organizations can benefit from this perspective. Methodology: The RBV framework was used to delimit the review so that the research method used in this paper is an empirical approach through a study of journals and supporting journals related to the topic under study. This paper evaluated and reviewed several empirical studies in terms of methodology and strategy that used to apply and implement the resourcebased view theory to improve the service based view quality of students' retention. Many articles indicated quantitative methods as the method strategy, but restrictions showed qualitative and mixed methods that should be concerned in future research. Findings: This article's literature search aimed at obtaining a usable sample of recently published papers to provide a sense of the conceptual gaps, knowledge gaps, methodological gaps and problem gaps in several resource-based (RBV) industries, but lesser are using in education. The dynamics and heterogeneity in this field of science encourage university researchers to develop and strengthen RBV theory. With this development, the concepts and theories of management are expected to be useful for academics. Recommendation & Limitation: On the critical reviews above, specific recommendations may in future serve as the key to enriching resource-based views. In this article, mixed and qualitative methods should be used to obtain accurate results. Additional attention should be paid to future research into higher education institutional resources, and integrate tangible and intangible resources into organizational capacity. Conclusion & Contribution: Resource-based view theory appears to have the capability to leverage resources and create more opportunities with fewer funds when applied to urban systems. One of the biggest contributions of this article is the direct strategy of scholars towards empirical studies and finding of resources as an essential antecedent to service quality and end to educational performance